Implementation of the Al-Qosimi Method in Tahfidzul Qur'an Learning at SMA Muhammadiyah Surakarta - Wulandayu, Nurya Putri; Istanto, Istanto (Tarbiyah Wa Ta'lim: Jurnal Penelitian Pendidikan dan Pembelajaran, 2024)
The Qur'an, as the holy book of Muslims and the greatest miracle, has invaluable value because it is the main guide in spiritual and worldly life. The tradition of mastering the Qur'an as a spiritual practice has been an integral part of Islam since the time of the Prophet Muhammad SAW. The Al - Qosimi method has been proven to be one of several efficient approaches in increasing efficiency in mastering the Qur'an. The aim of this research is to find out how to apply the Al-Qosimi method in learning tahfidzul Qur'an at SMA Muhammadiyah 2 Surakarta. This research uses qualitative field research and uses a phenomenological approach, with data collection techniques in the form of interviews, observation and documentation. The results of the research show that the Al - Qosimi method plays an important role in implementing mastery of the Qur'an for students at SMA Muhammadiyah 2 Surakarta. However, the obstacles faced include a lack of time to master and introduce the method to students. The positive impact of applying this method can be seen from the achievement of good memorization of the Qur'an, where the majority of them have succeeded in mastering juz 30 well, where SMA Muhammadiyah 2 Surakarta has graduated 17 children with memorizing the most 6 juz and the least juz 30 Thus, the Al-Qosimi method can be used as an efficient guide in mastering the Qur'an.